The Role of Government, Financial Literacy and Inclusion on MSME Finacial Performance - Muhammad Istan (Politeknik Ganesha Medan, 2023)
Financial literacy is the community's knowledge, beliefs, and skills to have basic economic concepts to run a business. Financial literacy must be accompanied by financial inclusion in the use of technology and financial facilities for the community. In running their business, MSMEs must know financial literacy and inclusion. The government fully supported MSMEs in Indonesia after the pandemic and experienced a decline in economic activity. This research was conducted to see how the influence of financial literacy, financial inclusion, and government support on the performance of MSMEs. The method is carried out with a literature review of 8 studies related to the performance of MSMEs. The qualitative descriptive process is carried out with different types of sampling. Of the eight studies conducted, it is illustrated that financial literacy and inclusion significantly affect the performance of an MSME. The government in every region in Indonesia always supports the progress of an MSME. However, knowledge about financial literacy and inclusion has been unevenly distributed in Indonesia. Human resource improvement must also be carried out on MSMEs so that the performance of MSMEs can be evenly distributed throughout Indonesia.